Kesadaran Halal Pelaku Umkm Terhadap Produk Olahan Wajib Bersertifikat Halal ( Studi Umkm Kecamatan Kwanyar) - Aditya, Wahyu; Hammam (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2024)
This research aims to analyse perception and awareness of Micro, Small and Medium Enterprises (MSMEs) for processed products that must be Halal certified. Halal Certificate has been an important issue in the food and beverage industry, due to the increase of consumer demand for products that comply with halal principles. This research method includes qualitative methods towards some MSMEs in Kwanyar Sub District in various sectors related to halal processed products. The data was obtained through an interview which included questions about the knowledge of halal certification, perceptions of the value of halal certification, and the impact felt after obtaining halal certification. The analysis’ result show that most of the MSMEs in Kwanyar Sub District have enough knowledge about Halal certificates, although there are still some MSMEs who do not understand Halal certification, with the majority of MSMEs believe that this certificate is able to increase consumer and open up a wider market opportunities. The impact of obtaining Halal certificate can be seen in increasing sales and market share for MSMEs that have been certified. Besides, Halal processed products tend to get more positive responses from consumers. However, there is a need for the more intensive educational approach and government’s support in the form of incentive or facilitation for helping MSMEs overcome obstacles related to halal certification. The enhancement and support are able to facilitate the participation of MSMEs on Halal certificate process, which will ultimately support the growth and sustainability of their business in an increasingly competitive market.